Lithuanian School of Photography in the Context of Soviet Ideology About the Doctoral Dissertation ("The sovietization of expression and dissemination of Lithuanian photography" by Margarita Matulytė) - Drėmaitė, Marija (Lietuvos istorijos studijos, 2011)
-